2008
DOI: 10.5713/ajas.2008.60320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Synthetic Lysine Sources on Growth Performance, Nutrient Digestibility and Nitrogen Retention in Weaning Pigs

Abstract: We compared the effects of supplementing L-lysine⋅SO 4 to L-lysine⋅HCl on growth performance, nutrient digestibility and nitrogen retention in weaning pigs. A total of 96 crossbred pigs, weaned at 21±3 days of age and with an average initial body weight (BW) 6.23±0.01 kg, were given one of 4 treatments, which translated into 6 replicates of 4 pigs in each pen. The animals were randomly assigned to four dietary treatments according to a randomized completely block design (RCBD) as follows: 1) control-no synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The efficacy of this essential amino acid in non-ruminant and ruminant nutrition was recently reviewed in two previous opinions (EFSA FEEDAP Panel, 2013, 2014 Since the mid-1980s, several studies have been carried out in non-ruminant animals to compare the efficacy of the different L-lysine forms (sulphate vs. monohydrochloride). From a general standpoint it can be concluded that the dietary supplementation either with L-lysine HCl (standard L-lysine source) or L-lysine sulphate did not result in any significant difference with respect to growth parameters (average daily gain and food conversion rate), nutrient digestibility, nitrogen retention or carcass composition of piglets and pigs for fattening (Bourdon and Henry, 1985;Roth et al, 1994;Smiricky-Tjardes et al, 2004;Liu et al, 2007;Ju et al, 2008). Similar conclusions on the equivalence between L-lysine sulphate and L-lysine HCl can be drawn from studies on chickens for fattening (Liebert, 1995;Neme et al, 2001;Ahmad et al, 2007;Bobeck et al, 2013).…”
Section: Efficacymentioning
confidence: 99%
“…The efficacy of this essential amino acid in non-ruminant and ruminant nutrition was recently reviewed in two previous opinions (EFSA FEEDAP Panel, 2013, 2014 Since the mid-1980s, several studies have been carried out in non-ruminant animals to compare the efficacy of the different L-lysine forms (sulphate vs. monohydrochloride). From a general standpoint it can be concluded that the dietary supplementation either with L-lysine HCl (standard L-lysine source) or L-lysine sulphate did not result in any significant difference with respect to growth parameters (average daily gain and food conversion rate), nutrient digestibility, nitrogen retention or carcass composition of piglets and pigs for fattening (Bourdon and Henry, 1985;Roth et al, 1994;Smiricky-Tjardes et al, 2004;Liu et al, 2007;Ju et al, 2008). Similar conclusions on the equivalence between L-lysine sulphate and L-lysine HCl can be drawn from studies on chickens for fattening (Liebert, 1995;Neme et al, 2001;Ahmad et al, 2007;Bobeck et al, 2013).…”
Section: Efficacymentioning
confidence: 99%
“…L-lysine HCl, L-lysine sulphate and free lysine base) in monogastric animals. From a general standpoint, it can be concluded that dietary supplementation with either L-lysine HCl (standard L-lysine source) or L-lysine sulphate did not result in any significant difference with respect to growth parameters (average daily gain and feed conversion ratio), nutrient digestibility, nitrogen retention or carcass composition of piglets and pigs for fattening (Bourdon and Henry, 1985;Roth et al, 1994;Smiricky-Tjardes et al, 2004;Liu et al, 2007;Ju et al, 2008). Similar conclusions on the equivalence between L-lysine sulphate and L-lysine HCl can be drawn from studies on chickens for fattening (Liebert, 1995;Neme et al, 2001;Ahmad et al, 2007;Bobeck et al, 2013).…”
Section: Efficacymentioning
confidence: 99%